Thrombolysis and Thrombectomy in Acute Ischemic Stroke - Nam, Hyo Suk; Kim, Byung Moon (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
In the treatment of acute stroke, thrombolysis and thrombectomy have proven to be highly effective. Many patients have seen significant improvement after reperfusion therapy. This reprint aims to address current knowledge gaps and promote advancements in the use of thrombolysis and thrombectomy for the treatment of acute ischemic stroke.